Transducin-Like Enhancer of Split-6 (TLE6) Is a Substrate of Protein Kinase A Activity During Mouse Oocyte Maturation. Issue 3 (1st March 2014) - Duncan, Francesca E.; Padilla-Banks, Elizabeth; Bernhardt, Miranda L.; Ord, Teri S.; Jefferson, Wendy N.; Moss, Stuart B.; Williams, Carmen J.
Abstract: Fully grown oocytes in the ovary are arrested at prophase of meiosis I because of high levels of intraoocyte cAMP that maintain increased levels of cAMP-dependent protein kinase (PKA) activity. Following the luteinizing hormone surge at the time of ovulation, cAMP levels drop, resulting in a reduction in PKA activity that triggers meiotic resumption. Although much is known about the molecular mechanisms of how PKA activity fluctuations initiate the oocyte's reentry into meiosis, significantly less is known about the requirement for PKA activity in the oocyte after exit from the prophase I arrest. Here we show that although PKA activity decreases in the oocyte upon meiotic resumption, it increases throughout meiotic progression from the time of germinal vesicle breakdown (GVBD) until the metaphase II (MII) arrest. Blocking this meiotic maturation-associated increase in PKA activity using the pharmacological inhibitor H89 resulted in altered kinetics of GVBD, defects in chromatin and spindle dynamics, and decreased ability of oocytes to reach MII. These effects appear to be largely PKA specific because inhibitors targeting other kinases did not have the same outcomes. To determine potential proteins that may require PKA phosphorylation during meiosis, we separated oocyte protein extracts on an SDS-PAGE gel, extracted regions of the gel that had corresponding immune reactivity towards an anti-PKA substrate antibody, and performed mass spectrometry and microsequencing. Using this approach, we identified transducin-like enhancer of split-6 (TLE6)—a maternal effect gene that is part of the subcortical maternal complex—as a putative PKA substrate. TLE6 localized to the oocyte cortex throughout meiosis in a manner that is spatially and temporally consistent with the localization of critical PKA subunits. Moreover, we demonstrated that TLE6 becomes phosphorylated in a narrow window following meiotic resumption, and H89 treatment can completely block this phosphorylation when added prior to GVBD but not after. Taken together, these results highlight the importance of oocyte-intrinsic PKA in regulating meiotic progression after the prophase I arrest and offer new insights into downstream targets of its activity.